Pengembangan Profesi dan Karir Guru Dalam Mewujudkan Kualitas Pendidikan - Pratiwi, Inda; Azura, Yasmin; Nasution, Abdul Fattah; Hasibuan, Agus Salim (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Teacher professional and career development plays an important role in improving the quality of education. Teachers who have good professional and career skills can make a more significant contribution to the teaching and learning process and improve student learning outcomes. Therefore, teacher professional and career development must be the main focus in efforts to improve the quality of education. In the history of teacher professional and career development, it can be seen that efforts to improve the quality of education through developing teacher professionalism have been going on for a long time. This development is carried out through various programs and efforts, and the aim is to improve teacher competence and performance in the context of implementing the education and learning process in the classroom and outside the classroom. The teaching profession is a process that aims to develop teachers' professional abilities by adapting to educational demands. There are several basics in teacher professional development, including philosophical and pedagogical bases. Apart from that, teacher professional development must also be adjusted to the principles that have been established. Teacher professional and career development can be implemented through various programs. Both programs hosted by school institutions or teacher professional and career development programs launched by the government. With this teacher professional and career development program, it is hoped that teachers can actively participate in improving their respective competencies and skills.